Genetic Variability of the Noncoding Control Region of Cutaneous Merkel Cell Polyomavirus: Identification of Geographically Related Genotypes. (2nd February 2018) - Hashida, Yumiko; Higuchi, Tomonori; Matsui, Kiyohiko; Shibata, Yuka; Nakajima, Kimiko; Sano, Shigetoshi; Daibata, Masanori
Abstract : This study demonstrates that the noncoding control region (NCCR) of Merkel cell polyomavirus varies according to ethnicity. The 25-base pair duplication in the NCCR proved unique to Japanese persons, whereas other NCCR genotypes were prevalent worldwide. Abstract: Background: Merkel cell polyomavirus (MCPyV) is a ubiquitous cutaneous virus that causes Merkel cell carcinoma, which develops preferentially in white populations from Europe and North America. However, the genomic variations of MCPyV among ethnic groups have not been well delineated, and even less is known regarding alterations in the noncoding control region (NCCR) in the general population. Methods: MCPyV strains recovered from skin swab specimens from 250 healthy participants with distinct ethnicities and geographic origins were subjected to sequencing analysis of the NCCR. Results: A 25–base pair tandem repeat caused by a 25–base pair insertion within the NCCR was found predominantly in Japanese and East Asian individuals. Based on the presence of 2 other insertions and a deletion, the NCCR could be classified further into 5 genotypes. This tandem repeat was also found exclusively in the NCCR from Japanese patients with Merkel cell carcinoma, while other genotypes were detected in white patients from Europe and North America. Conclusions: Our results suggest that the MCPyV NCCR varies according to ethnicity and that assessing the short NCCR sequence provides a rapid and simple means for identification of the Japanese and East Asian variant genotype. It remains to be established whether these NCCR variations are associated differentially with the pathogenesis of MCPyV-driven Merkel cell carcinoma between regions with varying endemicity.